Let us dream : the path to a better future - Ivereigh, Austen (Simon & Schuster, 2020)
The leader of the Catholic Church discusses what the COVID-19 crisis revealed about the cruelty and inequality of society, what it can teach about handling upheaval, and how to make the world safer, fairer, and healthier for all people.